2005
DOI: 10.5194/bg-2-159-2005
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate and soil organic carbon dynamics in South Chilean Andisols

Abstract: Abstract. Extreme sensitivity of soil organic carbon (SOC) to climate and land use change warrants further research in different terrestrial ecosystems. The aim of this study was to investigate the link between aggregate and SOC dynamics in a chronosequence of three different land uses of a south Chilean Andisol: a second growth Nothofagus obliqua forest (SGFOR), a grassland (GRASS) and a Pinus radiata plantation (PINUS). Total carbon content of the 0-10 cm soil layer was higher for GRASS (6.7 kg C m −2 ) than… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
58
2
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 57 publications
13
58
2
9
Order By: Relevance
“…The absence of an aggregate hierarchy suggests that in volcanic ash soils aggregates are not predominantly stabilized by particulate organic matter. Formation and stabilization of aggregates is more likely to occur by electrostatic attractions among amorphous Al components and clay minerals in addition to metalhumus complexes acting as binding agents through ligand exchange between functional groups of soil C and Al (Nanzyo et al 1993;Huygens et al 2005). Comparable results have been reported in Chile, where no aggregate hierarchy was found in a volcanic ash soil.…”
Section: Sitesupporting
confidence: 58%
See 1 more Smart Citation
“…The absence of an aggregate hierarchy suggests that in volcanic ash soils aggregates are not predominantly stabilized by particulate organic matter. Formation and stabilization of aggregates is more likely to occur by electrostatic attractions among amorphous Al components and clay minerals in addition to metalhumus complexes acting as binding agents through ligand exchange between functional groups of soil C and Al (Nanzyo et al 1993;Huygens et al 2005). Comparable results have been reported in Chile, where no aggregate hierarchy was found in a volcanic ash soil.…”
Section: Sitesupporting
confidence: 58%
“…Huygens et al (2005) found no differences in the aggregate distribution of natural forest, grassland, and a pine plantation. The absence of an aggregate hierarchy suggests that in volcanic ash soils aggregates are not predominantly stabilized by particulate organic matter.…”
Section: Sitementioning
confidence: 85%
“…Research has shown that plantderived SOM is strongly degraded and that it is the microbial SOM fraction that contributes substantially to SOM pools in Andosols (Buurman et al, 2007). Stabilization of SOM in Andosols has been attributed to i) formation of the SOM in organo-mineral and/or organo-metallic (Al/Fe-humus) complexes (Inoue and Higashi, 1988;Nanzyo et al, 1993;Neculman et al, 2013;Percival et al, 2000;Rumpel et al, 2012;Torn et al, 1997), ii) low activity of soil microorganisms due to low soil pH, Al toxicity, low base cation content, and/or P deficiency (Tokashiki and Wada, 1975;Tonneijck, 2009), iii) physical protection of the SOM in stable microaggregates characteristic of variable charge soils (Huygens et al, 2005;Baldock and Broos, 2011), iv) sorption and deactivation of exoenzymes involved in the extracellular depolymerization component of SOM decomposition (Saggar et al, 1994;Miltner and Zech, 1998), v) burial of organic-rich surface horizons by repeated additions of airfall tephra deposition, and vi) the presence of microbiallyrecalcitrant charcoal (especially in melanic epipedons) (Miyazaki et al, 2009(Miyazaki et al, , 2010Nishimura et al, 2006). The stabilization of SOM is reflected in the 14 C age of humic acids extracted from A horizons of Andosols which is reported to range from modern to 30,000 YBP, with the majority in the range 1000-5000 YBP (Inoue and Higashi, 1988).…”
Section: Organic Carbon Accumulation In Andosolsmentioning
confidence: 99%
“…Recent studies reported an apparent lack of aggregate hierarchy in South American Andisols based on the absence of sizedependent changes in C concentration using the dispersion treatments commonly used for non-volcanic soils (Hoyos and Comerford 2005;Huygens et al 2005;Paul et al 2008;Candan and Broquen 2009). By applying 5-10-fold higher sonication energy following sodium saturation pretreatment, on the other hand, we were able to disrupt most of the macro-and microaggregates and found strong evidence of aggregate hierarchy present below the 53-μm scale for an allophanic Andisol (Asano and Wagai 2014).…”
Section: Introductionmentioning
confidence: 99%